Primary phytochemical studies of catunaregam spinosa (thunb.) Tirven for secondary metabolites - M. B. PATIL,; P. A. KHAN, (International Journal of Pharma and Bio Sciences, 2017)
Catunaregam spinosa (Thunb.) (Rubiaceae), commonly called as Gedhphal and madanaphala in Ayurveda. Various ethno medicinal aspects are present in folk literature and new scientific documentation. It has been reported that Catunaregam spinosa used in diarrhoea, dysentery and as abortifacient, anthelmintic and antipyretic. Phytochemical extraction was carried out for qualitative test for secondary metabolites presence in different part of C. spinosa. Plant was collected, parts are dried and fine powder was subjected to different solvent extraction with soxhlet apparatus. The result for test showed presence of Alkaloids, Cardiac glycosides, Coumarins, Flavonoids, Glycosides, Phenols, Reducing sugars, Saponins, Steroids, and Tannin in Leaves extract, Stem Bark extract and Root bark extract which varies according to variation in solvent system. Results reveals that the importance medicinal properties is due to the presence of these phyto-constituents which need to farther elaboration in future works to detect active ingredient for particular disease.